The Performative Body in the Virtual Environment of Video Games - Rastyam T. Aliev (Corpus Mundi)
This study focuses on the analysis of corporeality and its performativity in video games within the context of the player's interaction with digital nature. It examines games where nature acts as an active agent, influencing the bodily experiences of the character, such as fatigue, hunger, and adaptation to weather conditions. The application of Judith Butler's performativity theory helps to understand how corporeality in games is constructed through repetitive actions and interactions with the environment. The analysis includes the examination of gender representations, the deconstruction of binary oppositions, and the influence of interfaces on the player's perception of the body. The research demonstrates that corporeality in video games is a dynamic process that changes through interactions with nature and game mechanics, shaping unique forms of bodily experience. The findings contribute to understanding video games as a platform for rethinking corporeality and cultural norms.